2022
DOI: 10.47577/tssj.v27i1.5519
|View full text |Cite
|
Sign up to set email alerts
|

Reincarnation of MSMEs after the Government's Policy on Economic Recovery Due to the Covid-19 Pandemic in Indonesia

Abstract: Micro, Small, and Medium Enterprises (MSMEs) are experiencing a slump due to the COVID-19 pandemic, and it is feared that it will be challenging to get back up. At this time, the Indonesian government has issued policies through several ministries, including the Ministry of Finance and the Ministry of Health, to stabilize the national economy. Micro, Small, and Medium Enterprises (MSMEs) are the pillars of the national economy, so that this sector needs attention during this pandemic to reincarnate in a better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous research has found that fragmented systems above are a major impediment to aligning development needs at regional community and national levels (Crane, 1995;Zen, 2013). Pandemic Covid19 had influenced the social economic condition, including the capacity to finance the development of micro, small and medium enterprises (Abdullah, Fasiha, & Arno, 2020) The alignment between development planning (DP) and public budgeting (PB) has been considered as a major dimension of public budgeting regarding how an individual country seeks to finance its development plan (Chimhowu, Hulme, & Munro, 2019;Nwagwu, 1992;Thimmaiah, 1984). From the 1960s to the 1980s, the integration of both processes that involved technocratic or scientific approaches produced general directions for planning and budgeting that were adopted by the majority of developing and newly independent countries (Waterston, 1965;Gable & Laporte, 1983;Handa, 1984;Omolehinwa, 1989;Premchand, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that fragmented systems above are a major impediment to aligning development needs at regional community and national levels (Crane, 1995;Zen, 2013). Pandemic Covid19 had influenced the social economic condition, including the capacity to finance the development of micro, small and medium enterprises (Abdullah, Fasiha, & Arno, 2020) The alignment between development planning (DP) and public budgeting (PB) has been considered as a major dimension of public budgeting regarding how an individual country seeks to finance its development plan (Chimhowu, Hulme, & Munro, 2019;Nwagwu, 1992;Thimmaiah, 1984). From the 1960s to the 1980s, the integration of both processes that involved technocratic or scientific approaches produced general directions for planning and budgeting that were adopted by the majority of developing and newly independent countries (Waterston, 1965;Gable & Laporte, 1983;Handa, 1984;Omolehinwa, 1989;Premchand, 2001).…”
Section: Introductionmentioning
confidence: 99%